ANALISA STATUS KESUBURAN TANAH TANAMAN KELAPA SAWIT RAKYAT DI DESA HINAI KIRI, KECAMATAN SECANGGANG, KABUPATEN LANGKAT - Anggara, Diky; Hidayat, Fuad; Panggabean, Kevin Nicolas; Taulani, Ihsan; Pohan, Rafly Rasya Anugrah (Institute of Computer Science (IOCS), 2025)
Oil palm is crucial to the economy and ranks high among the most significant commodities. The oil palm tree can only grow in rich, fertile soil. Research An examination of the oil palm plantation's soil conditions in Hinai Kiri Village, Secanggang District, Langkat Regency, was the primary motivation for this study. Research In order to determine the soil's fertility, scientists examine its physical and chemical characteristics. At the Laboratory of the Indonesian Institute of Palm Technology, soil samples were collected from two depths: 0-20 cm also 20-40 cm.. Laboratory of the Indonesian Institute of Palm Technology. Based on the data, The soil texture was sandy and clayey clay loam, pore space 60% and 56%, bulk density 1.176 gr/ml and 1.156 gr/ml, and particle density 2.94 and 2.66 gr/ml. At field capacity, the moisture content rose to 25% and 28%, while under dry conditions, the levels were 4.16% and 8.6%. Technique technique of comparing soil with water and soil with KCl the soil's pH was calculated using. At a soil to water ratio of 1:2.5, the pH was 5.5, as well as at a soil to potassium chloride ratio of 1:2.5, it was 4.4, also at a ratio of 1:2.5, it was 5.9, based to the data. substance, dirt, also organic debris was 1.32% and 3.33%, while the value of C-Organic values were 0.77% and 1.94%. The soil condition shows organic matter is good and good for oil palm growth if proper management is done.